2018
DOI: 10.1139/cjz-2017-0255
|View full text |Cite
|
Sign up to set email alerts
|

Elk (Cervus elaphus) railway mortality in Ontario

Abstract: Wildlife railway research is highly underrepresented in science despite documented wildlife–train collision mortalities. Gathering baseline information is imperative to the development of effective train collision mitigation, especially for at-risk or small reintroduced populations such as elk (Cervus elaphus Linnaeus, 1758) in eastern North America. We tested our hypotheses that elk–train collision rates vary in relation to railway structure and weather by using a combination of radiotelemetry and railway mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…The effects of linear features on the movement of large terrestrial mammals are relatively well understood (Dyer et al, 2002; Whittington et al, 2004; Dickson et al, 2005; Latham et al, 2011; Whittington et al, 2011; McKenzie et al, 2012; Tremblay and Clair, 2009; DeMars et al, 2016; Dickie et al, 2017; Popp et al, 2018), but, here, we showed that anthropogenic linear features can also affect movement and space use of avian species during migration. Our approach was analytically nuanced, incorporating the affects of energy subsidies key to soaring movement into the the movement process.…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…The effects of linear features on the movement of large terrestrial mammals are relatively well understood (Dyer et al, 2002; Whittington et al, 2004; Dickson et al, 2005; Latham et al, 2011; Whittington et al, 2011; McKenzie et al, 2012; Tremblay and Clair, 2009; DeMars et al, 2016; Dickie et al, 2017; Popp et al, 2018), but, here, we showed that anthropogenic linear features can also affect movement and space use of avian species during migration. Our approach was analytically nuanced, incorporating the affects of energy subsidies key to soaring movement into the the movement process.…”
Section: Discussionmentioning
confidence: 56%
“…data ). Railways are, however, responsible for substantial mortality in large mammals (e.g., ungulates; Becker and Grauvogel, 1991; Gundersen and Andreassen, 1998; Popp et al, 2018), potentially concentrating carrion resources for migrating eagles. As both railway and road densities decline with increasing latitude in North America, they were included in models as an interaction with latitude in addition to their main effects.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations